2016
DOI: 10.1007/s11270-016-3146-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Groundwater Constituents on 1,4-Dioxane Degradation by a Binary Oxidant System

Abstract: The influence of groundwater on the degradation of 1,4-dioxane (dioxane) by siderite-activated hydrogen peroxide coupled with persulfate was investigated through a series of batch experiments. The degradation of dioxane was considerably slower in groundwater compared to the tests conducted with ultrapure water. Additional tests were conducted to examine potential inhibitory effects of selected ions in isolation. The inhibition effect of anions on dioxane degradation, from strongest inhibition to weakest, was: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
(33 reference statements)
0
6
0
Order By: Relevance
“…This is in contrast to other Fentonlike systems, which have been shown to be more sensitive to ionic composition. For example, Yan et al evaluated bicarbonate and calcium ions, which are often the most abundant ions in groundwater, and observed that they have a strong effect on dioxane degradation (Yan et al, 2016). These contrasting results indicate that the G-nZVI system is a robust medium for treatment of groundwater contaminated by TCA and similar compounds.…”
Section: Discussionmentioning
confidence: 99%
“…This is in contrast to other Fentonlike systems, which have been shown to be more sensitive to ionic composition. For example, Yan et al evaluated bicarbonate and calcium ions, which are often the most abundant ions in groundwater, and observed that they have a strong effect on dioxane degradation (Yan et al, 2016). These contrasting results indicate that the G-nZVI system is a robust medium for treatment of groundwater contaminated by TCA and similar compounds.…”
Section: Discussionmentioning
confidence: 99%
“…The results of recent research indicate that advanced oxidation processes implemented with activated persulfate, particularly in some combination with other oxidants, is effective for degradation of dioxane (e.g., Zhao et al, 2014;Zhong et al, 2015;Eberle et al, 2016;Yan et al, 2016). Very few studies have investigated the effectiveness of persulfate activation by natural aquifer materials (Sra et al, 2010;Liu et al, 2014), and these few studies have focused on oxidant activation and not on the efficacy of contaminant degradation nor on dioxane specifically.…”
Section: Introductionmentioning
confidence: 99%
“…Each of the oxidants have their advantages and disadvantages, which are discussed in detail in the preceding references. The use of persulfate has some advantages for subsurface applications, and it has been proven to be effective for the treatment of TCE (e.g., Liang et al 2004a; Liang et al 2004b) and dioxane (Zhong et al, 2015; Eberle et al 2016; Yan et al, 2016). …”
Section: Introductionmentioning
confidence: 99%